The potential for vertical bone regeneration via maxillary periosteal elevation. (11th November 2014) - Mouraret, Sylvain; Von Kaeppler, Ericka; Bardet, Claire; Hunter, Daniel J.; Chaussain, Catherine; Bouchard, Philippe; Helms, Jill A.
Abstract Background While many studies have been performed on the characteristics and regenerative capacity of long bone periosteum, the craniofacial periosteum remains poorly understood. Aim The aim of this study was to investigate the potential for a maxillary periosteum tunnelling procedure to induce vertical alveolar bone regeneration. Materials and Methods We employed a murine injury model that activates skeletal stem cells in the periosteum without overtly damaging the underlying cortical bone, preserving the integrity of the long bone and maxilla, and avoiding the introduction of pathological motion at the injury site. Further, we introduced a collagen sponge to serve as a scaffold, providing the necessary space for vertical bone regeneration. Results Periosteal elevation alone resulted in bone formation in the tibia and delayed bone resorption in the maxilla. With the presence of the collagen sponge, new bone formation occurred in the maxilla. Conclusions Periosteal response to injury varies with anatomical location, so conclusions from long bone studies should not be extrapolated for craniofacial applications. Murine maxillary periosteum has the osteogenic potential to induce vertical alveolar bone regeneration.